Profile of Mathematical Disposition of Junior High School Students in Mathematics Learning - Rahmawati Rahmawati; Zaenuri Zaenuri; Mulyono Mulyono; Adi Nur Cahyono (Universitas Negeri Semarang, 2022)
Abstrak. The success of students learning mathematics depends on their mathematical disposition. Students with a high mathematical disposition have a strong will and determination to learn. They are directly involved in the learning process so students can solve the problems they face confidently. Mathematical dispositions are not born instantly but result from long-term interactions, especially with mathematics teachers, during the learning process at school. This study aims to determine the mathematical disposition of junior high school students in the city of Banjarmasin. This type of research is survey research. The population in this study were students of class IX junior high school in the city of Banjarmasin. The sample in this study amounted to 65 students, with a sampling technique using purposive sampling. Data collection uses a mathematical disposition questionnaire containing 25 statement items. Descriptive statistical methods analyzed mathematical disposition questionnaire data. The results showed that the mathematical disposition of class IX junior high school students in Banjarmasin was 18.5% in the high category, 63.1% in the medium category, and 18.5% in the low category. As for the indicators of students' mathematical disposition, it shows that the high category is in the appreciation aspect, the medium category is on the indicators of flexibility, curiosity, metacognition, and application, while the indicators of self-confidence and persistence are in the low category.